Korean university students’ significant learning experiences and associated generic skills: A qualitative essay review - Lee, Ahram; Lee, Soo Jeung (Frontiers in Education, 2022)
The purpose of the present study was to explore significant learning experiences of Korean university students and examine associated generic skills. The study implemented a document analysis approach to investigate essays collected from 33 students in a 4-year university in Seoul, South Korea. A total of 102 excerpts were coded, forming 14 sub-themes which were categorized into five themes that describe students’ significant learning experiences. The five themes are interacting with others, learning by oneself and about oneself, realizing applicability to real-life, venturing into advanced learning, and experiencing a respectful learning atmosphere. Also, 18 generic skills were identified which were categorized into four clusters, namely comprehensive thinking skills, information utilization skills, interpersonal skills, and personal attributes. The results of the present study provide the groundwork for understanding students’ perceptions of significant learning experiences and associated generic skills.